2008
DOI: 10.2174/1874838400801010035
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Targeting Eosinophil Accumulation as a Novel Therapeutic Approach for Asthma

Abstract: Current therapies for asthma are aimed at controlling disease symptoms and for the majority of patients inhaled glucocorticoid anti-inflammatory therapy is both effective and well-tolerated. However, concerns remain about the adverse effects of glucocorticoids while a subset of asthmatic patients remains symptomatic despite optimal treatment thereby creating a clear unmet medical need. There is considerable evidence that implicates eosinophils as important effector cells and immunomodulators in the inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…The preferential accumulation of eosinophils in the asthmatic lung suggests the existence of pathways for their selective accumulation. This involves enhanced eosinophil production and release from the bone marrow followed by a combination of selective adhesion to the post‐capillary vascular endothelium and trans‐endothelial migration (TEM) into the surrounding tissues [6]. There is general agreement that the introduction of flow conditions to in vitro models of leucocyte adhesion is crucial to the generation of data relevant to the in vivo situation [7].…”
Section: Introductionmentioning
confidence: 99%
“…The preferential accumulation of eosinophils in the asthmatic lung suggests the existence of pathways for their selective accumulation. This involves enhanced eosinophil production and release from the bone marrow followed by a combination of selective adhesion to the post‐capillary vascular endothelium and trans‐endothelial migration (TEM) into the surrounding tissues [6]. There is general agreement that the introduction of flow conditions to in vitro models of leucocyte adhesion is crucial to the generation of data relevant to the in vivo situation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous animal studies have demonstrated essential roles for these cell adhesion molecules in the lung inflammation underlying asthma pathogenesis, including L-selectin, P-selectin, and E-selectin, ICAM-1 and VCAM-1, together with many of the α 1 and α 2 integrins [55] . These therefore represent potentially important therapeutic targets; these families of adhesion molecules have been under intense investigation by the pharmaceutical industry for the development of novel therapeutics.…”
Section: Targeting Cell Adhesion Moleculesmentioning
confidence: 99%